2017
DOI: 10.1037/rel0000073
|View full text |Cite
|
Sign up to set email alerts
|

Relational reasons for nonbelief in the existence of gods: An important adjunct to intellectual nonbelief.

Abstract: Can people who do not believe in a god or gods still be influenced by past or present emotional reactions to the concept of a deity? We asked self-labeled atheists (Study 1) and individuals holding atheistic and agnostic views (Study 2) to rate the extent to which their nonbelief was based on negative past relational experiences or negative current views regarding the character of a hypothetical god or gods. Among nonbelievers who reported some history of relational emotion toward or from a god or gods (76% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
(56 reference statements)
0
21
0
Order By: Relevance
“…Furthermore, religious struggle, just like the other forms of religiosity, occurs around the world and across different religious groups. Empirical studies confirm the existence of religious problems and tensions among Christians (Bryant and Astin 2008;Büssing et al 2013Büssing et al , 2016Büssing et al , 2017aBüssing et al , b, 2018Carter 2019;Łowicki and Zajenkowski 2017;Szcześniak et al 2019;Zarzycka 2018;Zarzycka et al 2017), Muslims (Abu-Raiya et al 2008, 2015, 2018Ai et al 2003), Jews (Abu-Raiya et al 2016;Pirutinsky et al 2011;Pirutinsky and Rosmarin 2018;Rosmarin et al 2009Rosmarin et al , 2017, Hindus (Benson et al 2011;Exline et al 2017;Simha et al 2013;Tarakeshwar et al 2003), and atheists or agnostic samples (Bradley et al 2016;Sedlar et al 2018).…”
Section: Religious Strugglementioning
confidence: 87%
“…Furthermore, religious struggle, just like the other forms of religiosity, occurs around the world and across different religious groups. Empirical studies confirm the existence of religious problems and tensions among Christians (Bryant and Astin 2008;Büssing et al 2013Büssing et al , 2016Büssing et al , 2017aBüssing et al , b, 2018Carter 2019;Łowicki and Zajenkowski 2017;Szcześniak et al 2019;Zarzycka 2018;Zarzycka et al 2017), Muslims (Abu-Raiya et al 2008, 2015, 2018Ai et al 2003), Jews (Abu-Raiya et al 2016;Pirutinsky et al 2011;Pirutinsky and Rosmarin 2018;Rosmarin et al 2009Rosmarin et al , 2017, Hindus (Benson et al 2011;Exline et al 2017;Simha et al 2013;Tarakeshwar et al 2003), and atheists or agnostic samples (Bradley et al 2016;Sedlar et al 2018).…”
Section: Religious Strugglementioning
confidence: 87%
“…In our sample of non-believers personal Intellect was negatively related to God's perceived Intellect and God's Emotional stability. Although the Intellect factor from the Big Five model is somewhat different than the Openness to experience factor measured within the Five Factor Model [76], [96] they are comparable and the research on nonbelievers [12] has shown that Openness was related to seeing God as more distant, whilst Rouse [73] showed atheists depict Jesus as being lower on Emotional stability then believers did. This suggests that the more people deemed themselves to be creative, imaginative, reflective and analytical the less they tend to perceive God to be like themselves and tend to judge God to be more emotionally unstable and characterized as envious, emotional, and moody.…”
Section: Discussionmentioning
confidence: 85%
“…Although several studies used the Big five or the Five factor model (FFM) to assess the perceived personality of Jesus [26], [71], [90], God [17] or various other religious figures and concepts [81] of both believers and non-believers [12], [73] none of the researchers so far have examined that the measure conforms to the predicted Five factor model. Although we can presume that the measures would be applicable even to the concept of God, as it is the case when using a measure in a new language, in a new culture or on a new and previous unstudied demographic the presumption of the applicability of the scale should be tested before interpreting its relation between to other scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this logic, some atheists endorse a history of negative emotions toward god(s) as a reason for their nonbelief (Bradley et al 2017;Bradley et al 2018). Along similar lines, in his writings about beliefs in God, Barrett (2004) has distinguished between reflective beliefs that are formed slowly, deliberately, and consciously, and nonreflective beliefs that are produced automatically and may be less explicit and less conscious.…”
Section: Religious and Spiritual Strugglesmentioning
confidence: 78%